GENESIS OF ADAPTIVE SYSTEMS AND PERSONALIZED TEACHING STRATEGIES IN EDUCATION (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the origins (genesis), developmental stages, and conceptual foundations of adaptive learning systems (Adaptive Learning) and personalized teaching strategies, which are among the most relevant directions of contemporary digital education. The study scientifically examines the evolution from behaviorist programmed instruction to modern models based on artificial intelligence and Educational Data Mining. In addition, the fundamental components of adaptive learning architecture—namely the Expert Model, Learner Model, and Adaptation Model—are analyzed, and their pedagogical significance in enhancing learning effectiveness is substantiated.
Keywords: Adaptive learning, personalized teaching, genesis, programmed instruction, artificial intelligence, Intelligent Tutoring Systems (ITS), Learner Model, Cognitive Load Theory, Educational Data Mining.